2021
DOI: 10.2478/cee-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

A Generating - Absorbing Boundary Condition Applied to Wave - Current Interactions Using the Method of Fundamental Solutions

Abstract: The purpose of this work is to study the feasibility and efficiency of Generating Absorbing Boundary Conditions (GABCs), applied to wave-current interactions using the Method of Fundamental Solutions (MFS) as radial basis function, the problem is solved by collocation method. The objective is modeling wave-current interactions phenomena applied in a Numerical Wave Tank (NWT) where the flow is described within the potential theory, using a condition without resorting to the sponge layers on the boundaries. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It can be shown that this constant is proportional to the maximum velocity of the earthquake. This observation, showing the close relationship between maximum velocity and maximum shear, was first noted several decades ago [7,8]. Next the variation of the normalized shear over all locations in the building, 0 ≤ x/L ≤ 1, will be shown for a range of natural periods, and for the damping h (0) = 0.20.…”
Section: Civil and Environmental Engineeringsupporting
confidence: 63%
See 2 more Smart Citations
“…It can be shown that this constant is proportional to the maximum velocity of the earthquake. This observation, showing the close relationship between maximum velocity and maximum shear, was first noted several decades ago [7,8]. Next the variation of the normalized shear over all locations in the building, 0 ≤ x/L ≤ 1, will be shown for a range of natural periods, and for the damping h (0) = 0.20.…”
Section: Civil and Environmental Engineeringsupporting
confidence: 63%
“…It is noted that the equivalent constant damping value h (0) is higher than the average of the variable damping. This is because h (0) is a weighted average, as noted after (8), with greater weight given to smaller wave speeds, which according to Figure 1, corresponds to larger x at the upper portions of the building.…”
Section: Examplementioning
confidence: 92%
See 1 more Smart Citation
“…Loukili et al [72] have developed a wave current interaction method that uses the Numerical Wave Tank flow to carry out the predictions of computer flow. Such concept is being used in detection of vibroacoustic signatures if any damage along the pavement structure exists.…”
Section: Traffic Monitoringmentioning
confidence: 99%
“…In addition, the numerical simulation using sponge layer boundary condition is mostly used, and then it is not efficient for several actual cases like truncated domains. For this reason, the Generating Absorbing Boundary Conditions (GABCs) [41,42] is strongly recommended to investigate easily the wave-current-structure interaction where the wave and current are coplanar, and opposite.…”
Section: Conclusion and Remarksmentioning
confidence: 99%